Force of evil [videorecording (DVD)] - Polonsky, Abraham; Garfield, John; Windsor, Marie; Gomez, Thomas, 1905-1971; Wolfert, Ira, 1908-1997 (Olive Films, 2012)
A lawyer whose connection to a ruthless racketeer has nearly destroyed his sense of morality. His participation in a rigged numbers racket could prove disastrous for his high-strung brother whose small-time policy bank stands to go broke when the rigged numbers pay off.